Hematophagocytic syndrome and malignancy: an unexplored relationship (Research, Society and Development, 2022)
The aim of this study was verify the relationship and implications of neoplasms as triggers for macrophage hyperactivation in secondary hemophagocytic lymphohistiocytosis. A bibliographic survey was carried out on the PubMed platform with selection of relevant articles on the proposed topic using the descriptors “hemophagocytic lymphohistiocytosis” AND “oncology”, including articles published until June 2019. describing the evolution of publications over the years, the modalities of published studies, and selecting clinical studies for description and detail. A total of 4504 published works were found, since 1952. It was observed that there was an increase in the number of publications from the 1990s, especially from 1997. The largest number of publications occurred in 2019. There is still a scarcity of publications on clinical studies on the subject, most of which focus on pediatric populations and patients with hematological tumors. It also demonstrates better benefits in the use of allogeneic hematopoietic stem cell transplantation, in addition to suggesting a change in the diagnostic parameter. Knowing conditions that may be related to oncological disease can improve the comprehensive care of these patients.